Iminium ion cascade reaction in the total synthesis of (+)-vincadifformine - Pandey, Ganesh; Kumara, Prasanna C. (Organic Letters, 2011)
An iminium ion triggered cascade reaction is described in the total synthesis of (+)-vincadifformine by the coupling of 3,3-substituted tetrahydropyridine and indole derivative. The strategy allows simultaneous construction of two new rings, three new sigma bonds, and two new stereogenic centers in one pot with complete stereochemical control.